You can finish taking the logarithms and see what falls out. You know that

log(ax^b) = log(a) + b*log(x)

Using this, you can simplify your expression as follows

5log(2x) - log(x) - log(4x^2)

= 5(log(2) + log(x)) - log(x) - (log(4) + 2log(x))

= 5log(2) - log(4) + 5log(x) - log(x) - 2log(x)

We know 4 = 2^2, so log(4) = 2log(2).

= 3log(2) + 2log(x)

= log(2^3*x^2)

=

All you can do is simplify the expression. There is not enough information to determine a value for x.

log(ax^b) = log(a) + b*log(x)

Using this, you can simplify your expression as follows

5log(2x) - log(x) - log(4x^2)

= 5(log(2) + log(x)) - log(x) - (log(4) + 2log(x))

= 5log(2) - log(4) + 5log(x) - log(x) - 2log(x)

We know 4 = 2^2, so log(4) = 2log(2).

= 3log(2) + 2log(x)

= log(2^3*x^2)

=

**log(8x^2)**All you can do is simplify the expression. There is not enough information to determine a value for x.